Childhood Polyarthritis As Early Manifestation of Autoimmune Polyendocrinopathy with Candidiasis and Ectodermal Dystrophy Syndrome - Gutierrez, Maria J.; Gilson, Julieta; Zacharias, Jamie; Ishmael, Faoud; Bingham, C. April (Frontiers in Immunology, 2017)
Autoimmune Polyendocrinopathy with Candidiasis and Ectodermal Dysplasia (APECED) is a rare disorder of immune dysregulation caused by mutations in the Autoimmune Regulator (AIRE) gene. Individuals affected with APECED develop a clinical syndrome characterized by ectodermal abnormalities, autoantibody production and organ-specific autoimmune manifestations. Inflammatory arthritis is usually not described as part of the syndrome and only sporadic cases are reported. We describe the case of a preschool-age girl who presented with hypoparathyroidism, hepatitis, interstitial pneumonitis, and chronic polyarthritis at 4 years of age, found to have two compound heterozygous disease-associated mutations in the AIRE gene. We also conducted a literature review of the main characteristics of inflammatory arthritis in APECED patients. Our case and review demonstrate that 1) Inflammatory arthritis, although rare, can be an early manifestation of APECED; 2) The diagnosis of APECED should be considered if mucocutaneous candidiasis, multiple organ-specific autoimmune manifestations, polyendocrinopathy, especially hypoparathyroidism or adrenal failure, or ectodermal dysplasia accompany joint symptoms; 3) Genotyping interpretation should take into account that mutations are found in the 14 exons of the gene, compound heterozygosity is common, and in some cases, only one or no mutated alleles are found.